Avaliação da concentração e dos tipos de flavonoides na própolis, utilizando métodos quimiométricos de classificação e calibração - Ariane Araujo Assimos (2014)
In this work, analytical methods were developed to assess the quality of commercial alcoholic extracts of propolis, based on chemometric methods such as Partial Least Squares Multivariate Calibration (PLS) and Partial Least Squares Discriminating Analysis (PLS-DA). Initially, the experimental conditions of the spectrophotometric method used for determining the concentration of flavonoids in propolis , which is a quality parameter regulated by MAPA (Ministério da Agricultura, Pecuária e Abastecimento) were optimized , so it could be applied to commercial extracts of propolis . The volume of sample used in the analysis, the concentration of aluminum nitrate and lithium acetate, and the type of solvent were evaluated. The UV-Vis spectra of the diluted samples were used for the construction of a PLS model for determining the concentration of flavonoids in the samples of propolis. The chemometric methodology proposed has shown to be very efficient in addition of be less time-consuming , laborious, and using a much smaller amount of reagent than the traditional spectrophotometric method . In the second part the UV-Vis spectra obtained previously were used for the construction of a PLS -DA model to classify the samples according to the type of phenolic compound. The constructed model was able to discriminate samples of commercial extracts of propolis in four classes according to the type and concentration of phenolic compounds and proved to be very useful for predicting which samples were irregular in concentration of flavonoids. Chromatographic analyzes were performed on representative samples of the classes observed in the PLS DA, and it was revealed that the main substances responsible for the separation in the four classes were the flavonoid pinocembrine and the phenolic acids artepillinC, p-coumaric acid and ferulic acid.